Customer retention in digital media business platforms in Malaysia / Mohd Remie Mohd Johan … [et al.] - Mohd Johan, Mohd Remie; Teoh, May Xyn; Abdul Manab, Nur Farhanah; Md Syed, Md Azalanshah; Mohd Adnan, Hamedi (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2020)
Firms in Malaysia are making a lot of efforts to retain their customers for as long as possible. Nonetheless, due to the overgrowing of other online shopping sites that are continually coming up with new features and benefits that are more attractive, this situation often causes customers to easily switch to other competitors which result in failure for firms to retain their customers. Therefore, a study on how digital media business platforms influence customer retention in Malaysia, targeting 303 respondents in Klang Valley was carried out. Pearson correlation test and multi regression were the statistical analysis methods adopted in this study. Through this research, we found that customer retention is positively impacted by customer awareness, customer satisfaction and customer engagement. This study concludes that when firms focus more on applying increased efforts in intensifying the awareness and satisfaction of the customers as well as the engagement between firms and customers, firms will experience a significant increase in their customer retention level.